A waterproof corrugated paperboard production process and its application in corrugated paperboard boxes

Through the process of modifying chitosan and adding antibacterial ingredients, the waterproof and antibacterial properties of corrugated cardboard are improved, and the problems of poor waterproofness and lack of antibacterial properties of corrugated cardboard are solved, and higher wear resistance and compressive resistance are achieved. It is suitable for packaging with high hygiene requirements such as food and medicine.

CN118390334BActive Publication Date: 2025-03-25NINGBO RIHE NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410573663.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-10
Publication Date
2025-03-25
Estimated Expiration
2044-05-10

AI Technical Summary

Technical Problem

Existing corrugated cardboard has poor water resistance, is prone to water absorption and deformation, and lacks antibacterial properties, making it difficult to meet the packaging needs of food, medicine and other products that require high sanitary conditions.

Method used

A waterproof corrugated cardboard production process is adopted, and the modification is made by adding monoamine propyl polydimethylsiloxane, hexamethylene diisocyanate trimer and chitosan acetic acid solution to form a chitosan-essential oil composite liquid, and mixed with antibacterial applicator and mixed additives, and then sprayed on the surface of the surface paper and pressed with the V-shaped corrugated core.

Benefits of technology

It significantly improves the waterproof and antibacterial properties of corrugated cardboard, enhances its wear resistance and compressive resistance, and meets the packaging needs with high requirements for sanitary conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention provides a waterproof corrugated board production process and its application in corrugated paperboard boxes, belonging to the technical field of packaging materials; its production process includes the following steps: adding monoaminopropyl polydimethylsiloxane to prepare a modified chitosan mixed solution; adding the modified chitosan mixed solution and stirring and mixing; adding chloroacetic acid to react and prepare an antibacterial sizing agent; adding 2,3-epoxypropyltrimethylammonium chloride to prepare a mixed additive; adding a mixed additive to prepare facial paper and a V-shaped corrugated core; spraying an antibacterial sizing agent and pressing. The present invention is modified by chitosan, and the hydrophobic properties of chitosan can be improved, and then the mixed emulsion made of gelatin, Elsholtzia essential oil, Litsea cubeba essential oil and Tween 80 is stirred and mixed to form a chitosan-essential oil composite liquid with a core-shell structure, which is added to the sizing agent, and sprayed on the surface of facial paper to make a corrugated board, and the waterproof and antibacterial properties of the obtained corrugated board can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of packaging materials, and in particular to a production process of waterproof corrugated paperboard and application thereof in corrugated paperboard boxes. Background Art

[0002] Corrugated cardboard is a cardboard material with a corrugated structure made from multiple layers of paper through a specific process. Its basic structure includes face paper, core paper and base paper. Due to its high strength, good cushioning performance, light weight and recyclability, it is widely used in the packaging of various products, such as home appliances, food, beverages, electronic products, daily necessities, express parcels, etc. It can also be used for non-packaging purposes such as display stands, billboards, and building templates.

[0003] However, since ordinary corrugated cardboard is mainly made of pulp, its essence is still an interwoven structure of cellulose fibers. Cellulose fibers themselves are hygroscopic and easy to absorb moisture, resulting in poor waterproofness of corrugated paper. It is easy to soften, deform, or even disintegrate in a humid environment. Moreover, since its surface and internal structure do not have the ability to inhibit or kill microorganisms such as bacteria and mold, under normal storage and use conditions, if corrugated paper is affected by moisture, pollution and other factors, it will breed microorganisms and affect its quality and service life. It is difficult to meet the use standards for packaging food, pharmaceutical products and other occasions with high requirements for hygiene conditions, resulting in its low applicability.

[0004] Therefore, we need to propose a production process of waterproof corrugated cardboard with antibacterial properties and its application in corrugated boxes to meet the usage standards for packaging food, pharmaceutical products and other scenarios and improve the applicability of corrugated boxes. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a waterproof corrugated paperboard production process and its application in corrugated paperboard boxes.

[0006] A production process for waterproof corrugated paperboard comprises the following steps:

[0007] S1: Add monoaminopropyl polydimethylsiloxane to prepare modified chitosan mixture

[0008] Dissolving monoaminopropyl polydimethylsiloxane and hexamethylene diisocyanate trimer in acetone respectively, stirring and mixing to react, and then adding the mixture to the chitosan acetic acid solution while stirring to react to obtain a modified chitosan mixed solution;

[0009] S2: Add modified chitosan mixture and stir to mix

[0010] The gelatin is dissolved and then mixed with Elsholtzia ciliata essential oil, Litsea cubeba essential oil and Tween 80 by high-speed shear homogenization, and then the modified chitosan mixed solution is added, stirred and mixed, and the pH is adjusted to obtain a chitosan-essential oil composite solution;

[0011] S3: Add chloroacetic acid to react and prepare an antibacterial sizing agent

[0012] Dissolving polyvinyl alcohol in water, adding hexamethylene diisocyanate for modification reaction, obtaining a modified polyvinyl alcohol solution for standby use, then mixing pea starch with sodium hydroxide solution for alkalization, adding chloroacetic acid for modification, and finally mixing with the modified polyvinyl alcohol solution, the chitosan-essential oil composite liquid, polyacrylate and water to obtain an antibacterial sizing agent;

[0013] S4: Add 2,3-epoxypropyltrimethylammonium chloride to prepare a mixed additive

[0014] After dissolving sodium hydroxide in anhydrous ethanol, corn starch is added to prepare starch slurry, and then 2,3-epoxypropyltrimethylammonium chloride is added to react, and finally the slurry is stirred and mixed with an aqueous epoxy resin solution and an imidazole solution to obtain a mixed additive;

[0015] S5: Adding mixed additives to prepare face paper and V-shaped corrugated core

[0016] After the waste paper pulp is diluted with deionized water, xylanase is added for heat preservation and enzymolysis, and then the waste paper pulp is mixed with eucalyptus pulp, wheat straw pulp and the above-mentioned mixed additives for pulping, and then calcium carbonate, kaolin and cellulose nanocrystals are added to make face paper and V-shaped corrugated core;

[0017] S6: Spraying antimicrobial sizing agent and pressing

[0018] The antibacterial sizing agent is sprayed evenly on the upper and lower surfaces of the surface paper, and quickly pressed with the V-shaped corrugated core, and after curing and drying, a corrugated board is obtained.

[0019] Furthermore, S1 specifically includes the following steps:

[0020] S1.1: Dissolve chitosan in 2% acetic acid solution at a solid-liquid ratio of 1 g: (20-30) mL, stir for 3-5 hours, and mix evenly to obtain chitosan acetic acid solution;

[0021] S1.2: dissolving monoaminopropyl polydimethylsiloxane and hexamethylene diisocyanate trimer in acetone respectively to prepare a monoaminopropyl polydimethylsiloxane solution with a mass fraction of 26-28% and a hexamethylene diisocyanate trimer solution with a mass fraction of 13-15%;

[0022] S1.3: Add the monoaminopropyl polydimethylsiloxane solution to an equal volume of hexamethylene diisocyanate trimer solution, and stir to react for 1-2 hours to obtain a reaction solution;

[0023] S1.4: Place the chitosan acetic acid solution in a reactor, add the reaction solution into the reactor with stirring at a volume ratio of chitosan acetic acid solution to reaction solution of 1:(2-3), and react for 2-3 hours to obtain a modified chitosan mixed solution.

[0024] Furthermore, S2 specifically includes the following steps:

[0025] S2.1: Gelatin is dissolved in 50°C distilled water at a solid-liquid ratio of 1g:(8-10)mL, and after stirring and mixing evenly, Elsholtzia ciliata essential oil, Litsea cubeba essential oil and Tween 80 are added at a solid-liquid ratio of 1g:(1-3)g:(0.1-0.2)g:(8-10)mL, and high shear homogenization and emulsification treatment is performed at a rate of 5000-6000r / min in a constant temperature water bath at 40-50°C to obtain a mixed emulsion;

[0026] S2.2: Place the mixed emulsion in a stirrer and stir at a rate of 500-600 r / min, add an equal volume of the modified chitosan mixed solution obtained in step S1.4, continue stirring for 20-30 min, then add sodium hydroxide solution to adjust the pH to 5.5-6.5 to obtain a precursor mixed solution;

[0027] S2.3: Place the above precursor mixture in an ice water bath at 3-5°C and continue stirring for 1-2 hours to obtain a chitosan-essential oil composite solution.

[0028] Furthermore, S3 specifically includes the following steps:

[0029] S3.1: Add polyvinyl alcohol to cold water, heat to 70-80°C, and stir until completely dissolved to obtain a transparent solution with a mass fraction of 4-6%;

[0030] S3.2: Keeping the temperature constant, add 1-2% hexamethylene diisocyanate to the above transparent solution while stirring, and stir to react for 3-4 hours to obtain a modified polyvinyl alcohol solution;

[0031] S3.3: Mix pea starch and ethanol at a solid-liquid ratio of 1 g: (10-20) mL and stir until evenly dispersed, then add sodium hydroxide solution and stir for 30-40 min to obtain an alkalized starch solution;

[0032] S3.4: Add chloroacetic acid to the alkalized starch solution, heat to 60-70°C, and stir to react for 5-6 hours, then wash and dry to obtain modified starch;

[0033] S3.5: By weight, 20-30 parts of modified polyvinyl alcohol solution and 20-30 parts of chitosan-essential oil composite liquid obtained in step S2.3 are stirred and mixed uniformly, and then 25-35 parts of modified starch, 45-55 parts of polyacrylate and 50-60 parts of water are added, and stirring and mixing are continued to obtain an antibacterial sizing agent.

[0034] Furthermore, S4 specifically includes the following steps:

[0035] S4.1: Dissolve sodium hydroxide in anhydrous ethanol at a solid-liquid ratio of 1 g: (40-50) mL, stir and mix evenly, then add corn starch at a solid-liquid ratio of (3-4) g: 1 mL, continue to stir and mix evenly, and obtain a starch slurry;

[0036] S4.2: Add 2,3-epoxypropyltrimethylammonium chloride accounting for 1 / 10 of the mass of corn starch to the above starch slurry, stir and mix evenly, then heat to 70-80°C, react for 6-7h, wash with anhydrous ethanol, and dry to obtain modified corn starch;

[0037] S4.3: Disperse the modified corn starch in deionized water at a solid-liquid ratio of 1g:(90-100)mL, add 1-3% by mass of an aqueous epoxy resin solution, stir and mix, then add an equal volume of 0.2-0.5% imidazole solution, continue stirring for 1-2h, and obtain a mixed additive.

[0038] Further, S5 includes the following steps:

[0039] S5.1: dilute the waste paper pulp with deionized water to a concentration of 10-20%, heat it to 60-70°C, add xylanase at a rate of (0.3-0.5) g / L, perform ultrasonic treatment for 1-2 hours, perform heat preservation and enzymolysis, filter and wash, and obtain pretreated paper pulp;

[0040] S5.2: By weight, 80-90 parts of eucalyptus pulp, 40-50 parts of wheat straw pulp, 105-125 parts of the pretreated pulp and 15-25 parts of the mixed additive prepared in step S4.3 are uniformly mixed and pulped, and then the pulp is boiled at 50-60° C. for 1-2 hours to obtain a mixed pulp liquid with a concentration of 6-8%;

[0041] S5.3: Add 8-12 parts of calcium carbonate, 3-5 parts of kaolin and 3-5 parts of cellulose nanocrystals to the above mixed pulp, mix evenly, and then perform papermaking, drying and curling as well as papermaking, drying, curling and corrugating with corrugating rollers to obtain face paper and V-shaped corrugated core.

[0042] Furthermore, the volume ratio of the sodium hydroxide solution to ethanol is 1:(2-4), the concentration of the sodium hydroxide solution is 5%, and the molar ratio of sodium hydroxide to chloroacetic acid is (2-3):1.

[0043] Furthermore, the mass ratio of the solution formed by dispersing the modified corn starch in deionized water to the aqueous epoxy resin solution is (12-16):1.

[0044] Furthermore, the thickness of the face paper is 0.3-0.5 mm, and the thickness and height of the V-shaped corrugated core are 0.2-0.3 mm and 0.4-0.6 mm, respectively.

[0045] The invention discloses an application of waterproof corrugated paperboard in corrugated paper boxes, which mainly comprises the following steps: after the corrugated paperboard prepared in step S6 is made into a corrugated paper box, the corrugated paper box can be used for packaging food, pharmaceutical products and other occasions with high requirements on sanitary conditions, so as to better ensure the sanitary safety of food and pharmaceutical products.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] 1. The present invention modifies chitosan by reacting a monoaminopropyl polydimethylsiloxane solution with a hexamethylene diisocyanate trimer solution, and then adding the chitosan acetic acid solution to carry out graft copolymerization reaction, thereby improving the hydrophobicity of chitosan. The chitosan is then stirred and mixed with a mixed emulsion made of gelatin, Elsholtzia ciliata essential oil, Litsea cubeba essential oil and Tween 80 to form a chitosan-essential oil composite liquid with a core-shell structure. Since the Elsholtzia ciliata essential oil and Litsea cubeba essential oil have a synergistic antibacterial effect, the Elsholtzia ciliata essential oil and Litsea cubeba essential oil are added to a sizing agent and sprayed on the surface of facial paper to form a corrugated board, thereby effectively improving the waterproof and antibacterial properties of the prepared corrugated board. In addition, due to the core-shell structure of the chitosan-essential oil composite liquid, the Elsholtzia ciliata essential oil and Litsea cubeba essential oil are coated in the chitosan graft copolymer, which can improve the stability of the essential oils, thereby further improving the antibacterial properties of the corrugated board.

[0048] 2. The present invention uses sodium hydroxide solution to alkalize pea starch, then adds chloroacetic acid to modify it, and then mixes it with modified polyvinyl alcohol, chitosan-essential oil composite liquid, polyacrylate and water to prepare an antibacterial sizing agent. Since the modified pea starch contains a linear structure with a relatively large molecular weight and a small degree of polymerization, the slurry formed by mixing with the modified polyvinyl alcohol, chitosan-essential oil composite liquid and polyacrylate has low viscosity and strong fluidity, and can easily penetrate into the inside of the facial paper to form a slurry film, and has excellent film-forming property and permeability. The introduction of hydroxyl groups improves the strength of the antibacterial sizing agent joint layer, thereby improving the wear resistance of the antibacterial sizing agent, and further effectively improving the wear resistance of the prepared corrugated board.

[0049] 3. The present invention modifies the corn starch by uniformly mixing corn starch with an ethanol solution of sodium hydroxide, then adding 2,3-epoxypropyltrimethylammonium chloride to react, and then stirring and mixing the modified corn starch with an aqueous epoxy resin and an imidazole solution to prepare a mixed additive, which is mixed with eucalyptus pulp, wheat straw pulp and pretreated paper pulp for pulping. Since the molecules of the modified corn starch contain hydroxyl groups and quaternary ammonium groups, hydrogen bonds can be formed with hydroxyl groups of eucalyptus fibers, wheat straw fibers and waste paper pulp fibers to improve the fiber bonding strength, thereby significantly improving the ring crush strength of the prepared face paper and V-shaped corrugated core, thereby enhancing the compressive resistance of the prepared corrugated board.

[0050] 4. In the present invention, since the cell wall of wheat straw fiber is thin and easily broken, more fine fibers and hydroxyl groups are exposed on the fiber surface, while the length distribution of eucalyptus fiber is uniform, and it is fully fibrillated and fine-fibrillated after pulping. Therefore, when eucalyptus pulp and wheat straw pulp are mixed for pulping, the bonding force between the fibers is enhanced, thereby further improving the bursting strength of the obtained face paper and V-shaped corrugated core, and further improving the wear resistance of the obtained corrugated board. DETAILED DESCRIPTION

[0051] The following is a detailed description of a waterproof corrugated paperboard production process and its application in corrugated paperboard boxes provided by the present invention in conjunction with specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternatives to implement some known technologies.

[0052] Example 1

[0053] A production process for waterproof corrugated paperboard comprises the following steps:

[0054] S1: Add monoaminopropyl polydimethylsiloxane to prepare modified chitosan mixture

[0055] Chitosan was dissolved in an acetic acid solution with a mass fraction of 2% at a solid-liquid ratio of 1g:20mL, stirred for 3h, uniformly mixed, and a chitosan acetic acid solution was obtained for standby use. Monoaminopropyl polydimethylsiloxane and hexamethylene diisocyanate trimer were dissolved in acetone respectively to prepare a monoaminopropyl polydimethylsiloxane solution with a mass fraction of 26% and a hexamethylene diisocyanate trimer solution with a mass fraction of 13%. The monoaminopropyl polydimethylsiloxane solution was then added to an equal volume of the hexamethylene diisocyanate trimer solution, stirred for reaction for 1h, and a reaction solution was obtained. Finally, the chitosan acetic acid solution was placed in a reactor, and the reaction solution was added to the reactor while stirring at a volume ratio of the chitosan acetic acid solution to the reaction solution of 1:2, and the reaction solution was reacted for 2h to obtain a modified chitosan mixed solution.

[0056] S2: Add modified chitosan mixture and stir to mix

[0057] Gelatin was dissolved in 50°C distilled water at a solid-liquid ratio of 1g:8mL, and after stirring and mixing evenly, Elsholtzia ciliata essential oil, Litsea cubeba essential oil and Tween 80 were added at a solid-liquid ratio of 1g:1g:0.1g:8mL, and high shear homogenization and emulsification treatment was performed at a rate of 5000r / min in a constant temperature water bath at 40°C to obtain a mixed emulsion, and then the mixed emulsion was placed in a blender and stirred at a rate of 500r / min, and an equal volume of the above-mentioned modified chitosan mixed solution was added at the same time, and stirring was continued for 20min, and then sodium hydroxide solution was added to adjust the pH to 5.5 to obtain a precursor mixed solution, and finally, the precursor mixed solution was placed in an ice water bath at 3°C ​​and stirred for 1h to obtain a chitosan-essential oil composite liquid;

[0058] S3: Add chloroacetic acid to react and prepare an antibacterial sizing agent

[0059] Add polyvinyl alcohol into cold water, heat to 70°C, and stir until completely dissolved to obtain a transparent solution with a mass fraction of 4%. Then, keep the temperature constant, add 1% hexamethylene diisocyanate to the transparent solution while stirring, and stir to react for 3 hours to obtain a modified polyvinyl alcohol solution for later use;

[0060] Pea starch and ethanol were stirred and mixed at a solid-liquid ratio of 1g:10mL, uniformly dispersed, and then sodium hydroxide solution was added, stirred and reacted for 30min to obtain an alkalized starch solution, wherein the volume ratio of the sodium hydroxide solution to the ethanol was 1:2, and the concentration of the sodium hydroxide solution was 5%. Subsequently, chloroacetic acid was added to the alkalized starch solution, heated to 60°C, and stirred and reacted for 5h, wherein the molar ratio of sodium hydroxide to chloroacetic acid was 2:1. After washing and drying, modified starch was obtained for standby use;

[0061] Finally, by weight, 20 parts of the modified polyvinyl alcohol solution and 20 parts of the chitosan-essential oil composite liquid are stirred and mixed uniformly, and then 25 parts of modified starch, 45 parts of polyacrylate and 50 parts of water are added, and stirring and mixing are continued to obtain an antibacterial sizing agent;

[0062] S4: Add 2,3-epoxypropyltrimethylammonium chloride to prepare a mixed additive

[0063] Sodium hydroxide was dissolved in anhydrous ethanol at a solid-liquid ratio of 1g:40mL, and after stirring and mixing, corn starch was added at a solid-liquid ratio of 3g:1mL, and the mixture was continued to be stirred and mixed to obtain a starch slurry, and then 2,3-epoxypropyltrimethylammonium chloride accounting for 1 / 10 of the mass of the corn starch was added to the starch slurry, and the mixture was stirred and mixed to obtain a starch slurry. The mixture was heated to 70°C, reacted for 6h, and then washed and dried with anhydrous ethanol to obtain a modified corn starch. Subsequently, the modified corn starch was dispersed in deionized water at a solid-liquid ratio of 1g:90mL, and a 1% water-based epoxy resin solution was added. After stirring and mixing, an equal volume of 0.2% imidazole solution was added, and stirring was continued for 1h to obtain a mixed additive, wherein the mass ratio of the solution formed by dispersing the modified corn starch in deionized water to the water-based epoxy resin solution was 12:1;

[0064] S5: Adding mixed additives to prepare face paper and V-shaped corrugated core

[0065] The waste paper pulp is diluted with deionized water to a concentration of 10%, then heated to 60°C, and 0.3 g / L of xylanase is added, ultrasonically treated for 1 hour, and heat-insulated and enzymolyzed, and then filtered and washed to obtain pretreated paper pulp for later use;

[0066] In parts by weight, 80 parts of eucalyptus pulp, 40 parts of wheat straw pulp, 105 parts of pretreated pulp and 15 parts of the above-mentioned mixed additives are uniformly mixed and pulped, and then the pulp is boiled at 50° C. for 1 hour to obtain a mixed pulp liquid with a concentration of 6%, and then 8 parts of calcium carbonate, 3 parts of kaolin and 3 parts of cellulose nanocrystals are added to the mixed pulp liquid, and after uniform mixing, papermaking, drying and curling treatment and papermaking, drying, curling treatment and corrugating roller corrugation are respectively carried out to obtain face paper and V-shaped corrugated core, wherein the thickness of the face paper is 0.3 mm, and the thickness and height of the V-shaped corrugated core are 0.2 mm and 0.4 mm;

[0067] S6: Spraying antimicrobial sizing agent and pressing

[0068] The antibacterial sizing agent is sprayed evenly on the upper and lower surfaces of the surface paper, and quickly pressed with the V-shaped corrugated core, and after curing and drying, a corrugated board is obtained.

[0069] The performance test results of the facial paper and V-shaped corrugated core are shown in Table 1 below:

[0070] 1. Determine the water absorption rate of the paper according to TAPP I standard T441om-09. Weigh the corrugated paperboard sample with the size of 100mm×100mm×0.5mm, and then place it between the base and the ring of the Cobb tester. Pour 100mL of water into the ring and measure the water absorption of the corrugated paperboard sample within 60s. Calculate the water absorption by the difference in mass before and after the test of each corrugated paperboard sample, and calculate the water absorption per unit area of ​​the corrugated paperboard sample (g / m 2)express;

[0071] 2. According to the revised AATCC100-2004 antibacterial test standard, a corrugated cardboard sample with a side length of 2.5 cm is placed on a flat plate, and 25 μL of bacterial solution is dripped on its surface. Then a piece of corrugated cardboard of the same specification is covered on the corrugated cardboard sample to make the corrugated cardboard sample fully contact with the bacteria. After 10 minutes, 5 mL of sodium thiosulfate solution with a concentration of 0.02 mol / L is added to the flat plate for quenching and vortexing to ensure that the bacteria are evenly dispersed in the solution. Then, it is continuously diluted with phosphate solution and plated. After culturing at 37°C for 24 hours, the residual colonies are counted, and then the antibacterial rate is calculated according to the formula: antibacterial rate = [(number of inoculated colonies - number of residual colonies) / number of inoculated colonies] × 100%;

[0072] 3. Test the bursting strength of the corrugated paperboard according to GB / T6545-1998 "Determination of bursting strength of paperboard" to reflect its wear resistance;

[0073] 4. Use a strength tester to test the ring compression strength of the corrugated cardboard in accordance with GB / T2679.8-1995 to reflect its compressive performance.

[0074] Example 2

[0075] A production process for waterproof corrugated paperboard comprises the following steps:

[0076] S1: Add monoaminopropyl polydimethylsiloxane to prepare modified chitosan mixture

[0077] Chitosan was dissolved in an acetic acid solution with a mass fraction of 2% at a solid-liquid ratio of 1g:25mL, stirred for 4h, uniformly mixed, and a chitosan acetic acid solution was obtained for standby use. Monoaminopropyl polydimethylsiloxane and hexamethylene diisocyanate trimer were respectively dissolved in acetone to prepare a monoaminopropyl polydimethylsiloxane solution with a mass fraction of 27% and a hexamethylene diisocyanate trimer solution with a mass fraction of 14%. The monoaminopropyl polydimethylsiloxane solution was then added to an equal volume of the hexamethylene diisocyanate trimer solution, stirred for reaction for 1.5h, and a reaction solution was obtained. Finally, the chitosan acetic acid solution was placed in a reactor, and the volume ratio of the chitosan acetic acid solution to the reaction solution was 1:2.5. The reaction solution was added to the reactor while stirring, and reacted for 2-3h to obtain a modified chitosan mixed solution.

[0078] S2: Add modified chitosan mixture and stir to mix

[0079] Gelatin was dissolved in 50°C distilled water at a solid-liquid ratio of 1g:9mL, and after stirring and mixing evenly, Elsholtzia ciliata essential oil, Litsea cubeba essential oil and Tween 80 were added at a solid-liquid ratio of 1g:2g:0.15g:9mL, and high shear homogenization and emulsification treatment was performed at a rate of 5500r / min in a constant temperature water bath at 45°C to obtain a mixed emulsion, and then the mixed emulsion was placed in a blender and stirred at a rate of 550r / min, and an equal volume of the above-mentioned modified chitosan mixed solution was added at the same time, and stirring was continued for 25min, and then sodium hydroxide solution was added to adjust the pH to 6 to obtain a precursor mixed solution, and finally, the precursor mixed solution was placed in an ice water bath at 4°C and stirred for 1.5h to obtain a chitosan-essential oil composite liquid;

[0080] S3: Add chloroacetic acid to react and prepare an antibacterial sizing agent

[0081] Add polyvinyl alcohol into cold water, heat to 75°C, and stir until completely dissolved to obtain a transparent solution with a mass fraction of 5%. Then, keep the temperature constant, add 1.5% hexamethylene diisocyanate to the transparent solution while stirring, and stir to react for 3.5 hours to obtain a modified polyvinyl alcohol solution for later use;

[0082] Pea starch and ethanol were stirred and mixed at a solid-liquid ratio of 1g:15mL, and uniformly dispersed, and then sodium hydroxide solution was added, and stirred for 35 minutes to obtain an alkalized starch solution, wherein the volume ratio of the sodium hydroxide solution to the ethanol was 1:3, and the concentration of the sodium hydroxide solution was 5%. Subsequently, chloroacetic acid was added to the alkalized starch solution, heated to 65°C, and stirred for 5.5 hours, wherein the molar ratio of sodium hydroxide to chloroacetic acid was 2.5:1. After washing and drying, modified starch was obtained for standby use;

[0083] Finally, by weight, 25 parts of the modified polyvinyl alcohol solution and 25 parts of the chitosan-essential oil composite liquid are stirred and mixed uniformly, and then 30 parts of modified starch, 50 parts of polyacrylate and 55 parts of water are added, and stirring and mixing are continued to obtain an antibacterial sizing agent;

[0084] S4: Add 2,3-epoxypropyltrimethylammonium chloride to prepare a mixed additive

[0085] Sodium hydroxide was dissolved in anhydrous ethanol at a solid-liquid ratio of 1g:45mL, and after stirring and mixing, corn starch was added at a solid-liquid ratio of 3.5g:1mL, and stirring and mixing was continued to obtain starch slurry, and then 2,3-epoxypropyltrimethylammonium chloride accounting for 1 / 10 of the mass of corn starch was added to the starch slurry, and stirring and mixing was continued, and then heated to 75°C, reacted for 6.5h, washed with anhydrous ethanol, and dried to obtain modified corn starch, and then the modified corn starch was dispersed in deionized water at a solid-liquid ratio of 1g:95mL, and then a 2% mass fraction of water-based epoxy resin solution was added, and after stirring and mixing, an equal volume of 0.35% imidazole solution was added, and stirring was continued for 1.5h to obtain a mixed additive, wherein the mass ratio of the solution formed by the modified corn starch dispersed in deionized water to the water-based epoxy resin solution was 14:1;

[0086] S5: Adding mixed additives to prepare face paper and V-shaped corrugated core

[0087] The waste paper pulp is diluted with deionized water to a concentration of 15%, then heated to 65°C, and 0.4 g / L of xylanase is added, ultrasonically treated for 1.5 hours, and heat-insulated and enzymolyzed, and then filtered and washed to obtain pretreated paper pulp for later use;

[0088] In parts by weight, 85 parts of eucalyptus pulp, 45 parts of wheat straw pulp, 115 parts of pretreated pulp and 20 parts of the above-mentioned mixed additives are uniformly mixed and pulped, and then the pulp is boiled at 55° C. for 1.5 hours to obtain a mixed pulp liquid with a concentration of 7%, and then 10 parts of calcium carbonate, 4 parts of kaolin and 4 parts of cellulose nanocrystals are added to the mixed pulp liquid, and after uniform mixing, papermaking, drying and curling treatment and papermaking, drying, curling treatment and corrugating roller corrugation are respectively carried out to obtain face paper and V-shaped corrugated core, wherein the thickness of the face paper is 0.4 mm, and the thickness and height of the V-shaped corrugated core are 0.25 mm and 0.5 mm;

[0089] S6: Spraying antimicrobial sizing agent and pressing

[0090] The antibacterial sizing agent is sprayed evenly on the upper and lower surfaces of the surface paper, and quickly pressed with the V-shaped corrugated core, and after curing and drying, a corrugated board is obtained.

[0091] Then, referring to the performance test of the facial paper and the V-shaped corrugated core in Example 1, the results are shown in Table 1 below.

[0092] Example 3

[0093] A production process for waterproof corrugated paperboard comprises the following steps:

[0094] S1: Add monoaminopropyl polydimethylsiloxane to prepare modified chitosan mixture

[0095] Chitosan was dissolved in an acetic acid solution with a mass fraction of 2% at a solid-liquid ratio of 1g:30mL, stirred for 5h, uniformly mixed, and a chitosan acetic acid solution was obtained for standby use. Monoaminopropyl polydimethylsiloxane and hexamethylene diisocyanate trimer were dissolved in acetone respectively to prepare a monoaminopropyl polydimethylsiloxane solution with a mass fraction of 28% and a hexamethylene diisocyanate trimer solution with a mass fraction of 15%. The monoaminopropyl polydimethylsiloxane solution was then added to an equal volume of the hexamethylene diisocyanate trimer solution, stirred for reaction for 2h, and a reaction solution was obtained. Finally, the chitosan acetic acid solution was placed in a reactor, and the reaction solution was added to the reactor while stirring at a volume ratio of the chitosan acetic acid solution to the reaction solution of 1:3, and the reaction solution was reacted for 3h to obtain a modified chitosan mixed solution.

[0096] S2: Add modified chitosan mixture and stir to mix

[0097] Gelatin was dissolved in 50°C distilled water at a solid-liquid ratio of 1g:10mL, and after stirring and mixing evenly, Elsholtzia ciliata essential oil, Litsea cubeba essential oil and Tween 80 were added at a solid-liquid ratio of 1g:3g:0.2g:10mL, and high shear homogenization and emulsification treatment was performed at a rate of 6000r / min in a constant temperature water bath at 50°C to obtain a mixed emulsion, and then the mixed emulsion was placed in a blender and stirred at a rate of 600r / min, and an equal volume of the above-mentioned modified chitosan mixed solution was added at the same time, and stirring was continued for 30min, and then sodium hydroxide solution was added to adjust the pH to 6.5 to obtain a precursor mixed solution, and finally, the precursor mixed solution was placed in an ice water bath at 5°C and stirred for 2h to obtain a chitosan-essential oil composite solution;

[0098] S3: Add chloroacetic acid to react and prepare an antibacterial sizing agent

[0099] Add polyvinyl alcohol into cold water, heat to 80°C, and stir until completely dissolved to obtain a transparent solution with a mass fraction of 6%. Then, keep the temperature constant, add 2% hexamethylene diisocyanate to the transparent solution while stirring, and stir for 4 hours to obtain a modified polyvinyl alcohol solution for later use;

[0100] Pea starch and ethanol were stirred and mixed at a solid-liquid ratio of 1g:20mL, uniformly dispersed, and then sodium hydroxide solution was added, stirred and reacted for 40min to obtain an alkalized starch solution, wherein the volume ratio of the sodium hydroxide solution to the ethanol was 1:4, and the concentration of the sodium hydroxide solution was 5%. Subsequently, chloroacetic acid was added to the alkalized starch solution, heated to 70°C, and stirred and reacted for 6h, wherein the molar ratio of sodium hydroxide to chloroacetic acid was 3:1. After washing and drying, modified starch was obtained for standby use;

[0101] Finally, by weight, 30 parts of the modified polyvinyl alcohol solution and 30 parts of the chitosan-essential oil composite liquid are stirred and mixed uniformly, and then 35 parts of modified starch, 55 parts of polyacrylate and 60 parts of water are added, and stirring and mixing are continued to obtain an antibacterial sizing agent;

[0102] S4: Add 2,3-epoxypropyltrimethylammonium chloride to prepare a mixed additive

[0103] Sodium hydroxide was dissolved in anhydrous ethanol at a solid-liquid ratio of 1g:50mL, and after stirring and mixing, corn starch was added at a solid-liquid ratio of 4g:1mL, and the mixture was stirred and mixed to obtain a starch slurry. Then, 2,3-epoxypropyltrimethylammonium chloride accounting for 1 / 10 of the mass of the corn starch was added to the starch slurry, and the mixture was stirred and mixed to obtain a modified corn starch. Subsequently, the modified corn starch was dispersed in deionized water at a solid-liquid ratio of 1g:100mL, and a 3% water-based epoxy resin solution was added. After stirring and mixing, an equal volume of 0.5% imidazole solution was added, and stirring was continued for 2h to obtain a mixed additive, wherein the mass ratio of the solution formed by dispersing the modified corn starch in deionized water to the water-based epoxy resin solution was 16:1;

[0104] S5: Adding mixed additives to prepare face paper and V-shaped corrugated core

[0105] The waste paper pulp is diluted with deionized water to a concentration of 20%, then heated to 70°C, and 0.5 g / L of xylanase is added, ultrasonically treated for 2 hours, and heat-insulated and enzymolyzed, and then filtered and washed to obtain pretreated paper pulp for later use;

[0106] In parts by weight, 90 parts of eucalyptus pulp, 50 parts of wheat straw pulp, 125 parts of pretreated pulp and 25 parts of the above-mentioned mixed additives are uniformly mixed and beaten, and then the pulp is boiled at 60° C. for 2 hours to obtain a mixed pulp liquid with a concentration of 8%, and then 12 parts of calcium carbonate, 5 parts of kaolin and 5 parts of cellulose nanocrystals are added to the mixed pulp liquid, and after uniform mixing, papermaking, drying and curling treatment and papermaking, drying, curling treatment and corrugating roller corrugation are respectively carried out to obtain face paper and V-shaped corrugated core, wherein the thickness of the face paper is 0.5 mm, and the thickness and height of the V-shaped corrugated core are 0.3 mm and 0.6 mm;

[0107] S6: Spraying antimicrobial sizing agent and pressing

[0108] The antibacterial sizing agent is sprayed evenly on the upper and lower surfaces of the surface paper, and quickly pressed with the V-shaped corrugated core, and after curing and drying, a corrugated board is obtained.

[0109] Then, referring to the performance test of the facial paper and the V-shaped corrugated core in Example 1, the results are shown in Table 1 below.

[0110] Table 1: Summary of performance test results of Examples 1-3

[0111]

[0112] Comparative Example 1

[0113] The difference between this comparative example and Example 1 is that the modified chitosan mixed solution in step S2 is replaced by an equal amount of chitosan acetic acid solution in step S1, and then the performance test of the corrugated paperboard is carried out according to the performance test method in Example 1. The test results are shown in Table 2 below.

[0114] Comparative Example 2

[0115] The difference between this comparative example and Example 1 is that the Elsholtzia ciliata essential oil in step S2 is replaced by an equal amount of Litsea cubeba essential oil, and then the performance test of the corrugated board is carried out with reference to the performance test method in Example 1, and the test results are shown in Table 2 below.

[0116] Comparative Example 3

[0117] The difference between this comparative example and Example 1 is that the Litsea cubeba essential oil in step S2 is replaced with an equal amount of Elsholtzia ciliata essential oil, and then the performance test of the corrugated board is performed with reference to the performance test method in Example 1, and the test results are shown in Table 2 below.

[0118] Comparative Example 4

[0119] The difference between this comparative example and Example 1 is that the 20 parts of chitosan-essential oil composite liquid in step S3 are removed, and then the performance test of the corrugated board is carried out with reference to the performance test method in Example 1. The test results are shown in Table 2 below.

[0120] Table 2: Comparison of corrugated board performance test results of Example 1 and Comparative Examples 1-4

[0121]

[0122] From the performance test comparison between Comparative Example 1 and Example 1, it can be seen that the water absorption of the corrugated board in Comparative Example 1 is 56.23 g / m 2 , which is significantly higher than that of Example 1, indicating that the hydrophobic properties of chitosan can be improved by reacting a monoaminopropyl polydimethylsiloxane solution with a hexamethylene diisocyanate trimer solution and then adding the chitosan acetic acid solution to carry out a graft copolymerization reaction to modify chitosan;

[0123] From the performance test comparison of Comparative Examples 2-3 and Example 1, it can be seen that the antibacterial rates of the corrugated paperboards in Comparative Examples 2 and 3 are 87.4% and 85.1%, respectively, which are both lower than that in Example 1, indicating that the compound of Elsholtzia ciliata essential oil and Litsea cubeba essential oil has a synergistic antibacterial effect. After adding them to the sizing agent and spraying them on the surface of the face paper to make the corrugated paperboard, the antibacterial properties of the obtained corrugated paperboard can be effectively improved;

[0124] From the performance test comparison between Comparative Example 4 and Example 1, it can be seen that the water absorption of the corrugated board in Comparative Example 4 is 56.25 g / m 2 , which is significantly higher than that in Example 1, while the antibacterial rate of the facial tissue in Comparative Example 4 is 0, which is significantly lower than that in Example 1, indicating that the chitosan is modified by reacting a monoaminopropyl polydimethylsiloxane solution with a hexamethylene diisocyanate trimer solution, and then adding the chitosan acetic acid solution for graft copolymerization, and then stirring and mixing with a mixed emulsion made of gelatin, Elsholtzia essential oil, Litsea cubeba essential oil and Tween 80 to form a chitosan-essential oil composite liquid with a core-shell structure, adding the composite liquid to the sizing agent, and spraying it on the surface of the facial tissue to form a corrugated board, which can effectively improve the waterproof and antibacterial properties of the prepared corrugated board.

[0125] Comparative Example 5

[0126] The difference between this comparative example and Example 1 is that the chitosan-essential oil composite liquid in S3 is replaced by an equal amount of modified chitosan mixed liquid and Elsholtzia ciliata essential oil and Litsea cubeba essential oil, wherein the mass ratio of Elsholtzia ciliata essential oil to Litsea cubeba essential oil is 1:1, and the volume ratio of the sum of the two to the modified chitosan mixed liquid is 1:1. Then, the obtained corrugated board is subjected to a performance test by referring to the performance test method in Example 1, and the results are shown in Table 3 below.

[0127] Table 3: Comparison of corrugated board performance test results of Example 1 and Comparative Example 5

[0128] project Antibacterial rate (%) Example 1 95.8 Comparative Example 5 79.3

[0129] From the performance test comparison between Comparative Example 5 and Example 1, it can be seen that the antibacterial rate of the corrugated board in Comparative Example 5 is 79.3%, which is significantly lower than 95.8% in Example 1. It can be seen that due to the core-shell structure of the chitosan-essential oil composite liquid, the Elsholtzia ciliata essential oil and the Litsea cubeba essential oil are encapsulated in the chitosan graft copolymer, which can improve the stability of the essential oil, thereby further improving the antibacterial performance of the corrugated board.

[0130] Comparative Example 6

[0131] The difference between this comparative example and Example 1 is that 25 parts of modified starch in step S3 are replaced by an equal amount of pea starch, and then the performance test method in Example 1 is referred to to perform a performance test on the obtained corrugated paperboard, and the results are shown in Table 4 below.

[0132] Table 4: Comparison of corrugated board performance test results of Example 1 and Comparative Example 6

[0133] project Bursting strength(KPa) Example 1 2583 Comparative Example 6 1765

[0134] From the performance test comparison of Comparative Example 6 and Example 1, it can be seen that the bursting strength of the corrugated board in Comparative Example 6 is 1765 KPa, which is significantly lower than 2583 KPa in Example 1. It can be seen that the antibacterial sizing agent is prepared by alkalizing pea starch with sodium hydroxide solution, adding chloroacetic acid for modification, and then mixing with modified polyvinyl alcohol, chitosan-essential oil composite liquid, polyacrylate and water. Since the modified pea starch contains a linear structure with a large molecular weight and a small degree of polymerization, the slurry formed by mixing with modified polyvinyl alcohol, chitosan-essential oil composite liquid and polyacrylate has low viscosity and strong fluidity, and is easy to penetrate into the inside of the face paper to form a slurry film, and has excellent film-forming and permeability. The introduction of hydroxyl groups improves the strength of the antibacterial sizing agent joint layer, thereby improving the wear resistance of the antibacterial sizing agent, and further effectively improving the wear resistance of the prepared corrugated board.

[0135] Comparative Example 7

[0136] The difference between this comparative example and Example 1 is that the mixed additive in step S5 is removed, and then the performance test of the corrugated board is carried out with reference to the performance test method of Example 1. The results are shown in Table 5 below.

[0137] Table 5: Comparison of corrugated board performance test results of Example 1 and Comparative Example 7

[0138] project Ring compression strength (N / m) Example 1 6926 Comparative Example 7 4213

[0139] From the performance test comparison between Comparative Example 7 and Example 1, it can be seen that the ring crush strength of the corrugated board in Comparative Example 7 is 4213 N / m, which is significantly lower than 6926 N / m of Example 1. It can be seen that the corn starch is modified by uniformly mixing corn starch with an ethanol solution of sodium hydroxide, and then adding 2,3-epoxypropyltrimethylammonium chloride to react. The modified corn starch is then stirred and mixed with an aqueous epoxy resin and an imidazole solution to prepare a mixed additive. After the mixed additive is mixed and pulped with eucalyptus pulp, wheat straw pulp and pretreated pulp, the modified corn starch can form hydrogen bonds with the hydroxyl groups of eucalyptus fiber, wheat straw fiber and waste pulp fiber due to the hydroxyl and quaternary ammonium groups in the molecules, thereby improving the fiber bonding strength, thereby significantly improving the ring crush strength of the prepared face paper and V-shaped corrugated core, and enhancing the compressive resistance of the prepared corrugated board.

[0140] Comparative Example 8

[0141] The difference between this comparative example and Example 1 is that the eucalyptus pulp and wheat straw pulp in step S5 are replaced by an equal amount of pretreated pulp, and then the performance test of the corrugated board is carried out according to the performance test method of Example 1, and the results are shown in Table 6 below.

[0142] Table 6: Comparison of the test results of facial paper performance of Example 1 and Comparative Example 8

[0143] project Bursting strength(KPa) Example 1 2583 Comparative Example 8 1679

[0144] From the performance test comparison between Comparative Example 8 and Example 1, it can be seen that the bursting strength of the corrugated board in Comparative Example 8 is 1679 KPa, which is significantly lower than 2583 KPa in Example 1. It can be seen that since the cell wall of wheat straw fiber is thin and easy to break, more fine fibers and hydroxyl groups are exposed on the fiber surface, while the length distribution of eucalyptus fiber is uniform, and it is fully fibrillated and fine-fibrillated after beating. Therefore, when eucalyptus pulp and wheat straw pulp are mixed for beating, the bonding force between fibers is enhanced, thereby further improving the bursting strength of the obtained face paper and V-shaped corrugated core, and then improving the wear resistance of the obtained corrugated board.

[0145] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for producing waterproof corrugated paperboard, characterized in that: The steps include: S1: Add monoaminopropyl polydimethylsiloxane to prepare modified chitosan mixture Dissolving monoaminopropyl polydimethylsiloxane and hexamethylene diisocyanate trimer in acetone respectively, stirring and mixing to react, and then adding the mixture to the chitosan acetic acid solution while stirring to react to obtain a modified chitosan mixed solution; S2: Add modified chitosan mixture and stir to mix The gelatin is dissolved and then mixed with Elsholtzia ciliata essential oil, Litsea cubeba essential oil and Tween 80 by high-speed shear homogenization, and then the modified chitosan mixed solution is added, stirred and mixed, and the pH is adjusted to obtain a chitosan-essential oil composite solution; S3: Add chloroacetic acid to react and prepare an antibacterial sizing agent Dissolving polyvinyl alcohol in water, adding hexamethylene diisocyanate for modification reaction, obtaining a modified polyvinyl alcohol solution for standby use, then mixing pea starch with sodium hydroxide solution for alkalization, adding chloroacetic acid for modification, and finally mixing with the modified polyvinyl alcohol solution, the chitosan-essential oil composite liquid, polyacrylate and water to obtain an antibacterial sizing agent; S4: Add 2,3-epoxypropyltrimethylammonium chloride to prepare a mixed additive After dissolving sodium hydroxide in anhydrous ethanol, corn starch is added to prepare starch slurry, and then 2,3-epoxypropyltrimethylammonium chloride is added to react, and finally the slurry is stirred and mixed with an aqueous epoxy resin solution and an imidazole solution to obtain a mixed additive; S5: Adding mixed additives to prepare face paper and V-shaped corrugated core After the waste paper pulp is diluted with deionized water, xylanase is added for heat preservation and enzymolysis, and then the waste paper pulp is mixed with eucalyptus pulp, wheat straw pulp and the above-mentioned mixed additives for pulping, and then calcium carbonate, kaolin and cellulose nanocrystals are added to make face paper and V-shaped corrugated core; S6: Spraying antimicrobial sizing agent and pressing The antibacterial sizing agent is sprayed evenly on the upper and lower surfaces of the surface paper, and quickly pressed with the V-shaped corrugated core, and after curing and drying, a corrugated board is obtained.

2. The method for producing a waterproof corrugated paperboard according to claim 1, characterized in that: Step S1 specifically includes the following steps: S1.1: Dissolve chitosan in 2% acetic acid solution at a solid-liquid ratio of 1 g: (20-30) mL, stir for 3-5 hours, and mix evenly to obtain chitosan acetic acid solution; S1.2: Dissolve monoaminopropyl polydimethylsiloxane and hexamethylene diisocyanate trimer in acetone respectively to prepare a monoaminopropyl polydimethylsiloxane solution with a mass fraction of 26-28% and a hexamethylene diisocyanate trimer solution with a mass fraction of 13-15%; S1.3: Add the monoaminopropyl polydimethylsiloxane solution to an equal volume of hexamethylene diisocyanate trimer solution, and stir to react for 1-2 hours to obtain a reaction solution; S1.4: Place the chitosan acetic acid solution in a reactor, add the reaction solution into the reactor with stirring at a volume ratio of chitosan acetic acid solution to reaction solution of 1:(2-3), and react for 2-3 hours to obtain a modified chitosan mixed solution.

3. The method for producing a waterproof corrugated paperboard according to claim 2, characterized in that: Step S2 specifically includes the following steps: S2.1: Dissolve gelatin in 50°C distilled water at a solid-liquid ratio of 1g:(8-10)mL, stir and mix evenly, then add Elsholtzia ciliata essential oil, Litsea cubeba essential oil and Tween 80 at a solid-liquid ratio of 1g:(1-3)g:(0.1-0.2)g:(8-10)mL, and perform high shear homogenization emulsification treatment at a rate of 5000-6000r / min in a constant temperature water bath at 40-50°C to obtain a mixed emulsion; S2.2: Place the mixed emulsion in a stirrer and stir at a rate of 500-600 r / min, add an equal volume of the modified chitosan mixed solution obtained in step S1.4, continue stirring for 20-30 min, then add sodium hydroxide solution to adjust the pH to 5.5-6.5 to obtain a precursor mixed solution; S2.3: Place the above precursor mixture in an ice water bath at 3-5°C and continue stirring for 1-2 hours to obtain a chitosan-essential oil composite solution.

4. The method for producing waterproof corrugated paperboard according to claim 3, characterized in that: Step S3 specifically includes the following steps: S3.1: Add polyvinyl alcohol to cold water, heat to 70-80°C, and stir until completely dissolved to obtain a transparent solution with a mass fraction of 4-6%; S3.2: Keeping the temperature constant, add 1-2% hexamethylene diisocyanate to the above transparent solution while stirring, and stir to react for 3-4 hours to obtain a modified polyvinyl alcohol solution; S3.3: Mix pea starch and ethanol at a solid-liquid ratio of 1 g: (10-20) mL and stir until uniformly dispersed, then add sodium hydroxide solution and stir for 30-40 minutes to obtain an alkalized starch solution; S3.4: Add chloroacetic acid to the alkalized starch solution, heat to 60-70°C, and stir to react for 5-6 hours, then wash and dry to obtain modified starch; S3.5: By weight, 20-30 parts of modified polyvinyl alcohol solution and 20-30 parts of chitosan-essential oil composite liquid obtained in step S2.3 are stirred and mixed uniformly, and then 25-35 parts of modified starch, 45-55 parts of polyacrylate and 50-60 parts of water are added, and stirring and mixing are continued to obtain an antibacterial sizing agent.

5. The method for producing waterproof corrugated paperboard according to claim 4, characterized in that: Step S4 specifically includes the following steps: S4.1: Dissolve sodium hydroxide in anhydrous ethanol at a solid-liquid ratio of 1 g: (40-50) mL, stir and mix evenly, then add corn starch at a solid-liquid ratio of (3-4) g: 1 mL, continue stirring and mixing evenly to obtain a starch slurry; S4.2: Add 2,3-epoxypropyltrimethylammonium chloride accounting for 1 / 10 of the mass of corn starch to the above starch slurry, stir and mix evenly, then heat to 70-80°C, react for 6-7h, wash with anhydrous ethanol, and dry to obtain modified corn starch; S4.3: Disperse the modified corn starch in deionized water at a solid-liquid ratio of 1g: (90-100)mL, add 1-3% by mass of an aqueous epoxy resin solution, stir and mix, then add an equal volume of 0.2-0.5% imidazole solution, continue stirring for 1-2h, and obtain a mixed additive.

6. The method for producing waterproof corrugated paperboard according to claim 5, characterized in that: S5 specifically includes the following steps: S5.1: dilute the waste paper pulp with deionized water to a concentration of 10-20%, heat it to 60-70°C, add xylanase at a rate of (0.3-0.5) g / L, perform ultrasonic treatment for 1-2 hours, perform heat preservation and enzymolysis, filter and wash, and obtain pretreated paper pulp; S5.2: By weight, 80-90 parts of eucalyptus pulp, 40-50 parts of wheat straw pulp, 105-125 parts of the pretreated pulp and 15-25 parts of the mixed additive prepared in step S4.3 are uniformly mixed and pulped, and then boiled at 50-60° C. for 1-2 hours to obtain a mixed pulp liquid with a concentration of 6-8%; S5.3: Add 8-12 parts of calcium carbonate, 3-5 parts of kaolin and 3-5 parts of cellulose nanocrystals to the above mixed pulp, mix evenly, and then perform papermaking, drying and curling as well as papermaking, drying, curling and corrugating with corrugating rollers to obtain face paper and V-shaped corrugated core.

7. The method for producing waterproof corrugated paperboard according to claim 4, characterized in that: The volume ratio of sodium hydroxide solution to ethanol is 1:(2-4), the concentration of sodium hydroxide solution is 5%, and the molar ratio of sodium hydroxide to chloroacetic acid is (2-3):

1.

8. The method for producing waterproof corrugated paperboard according to claim 5, characterized in that: The mass ratio of the solution formed by dispersing modified corn starch in deionized water to the aqueous epoxy resin solution is (12-16):

1.

9. The method for producing waterproof corrugated paperboard according to claim 6, characterized in that: The thickness of the face paper is 0.3-0.5mm, the thickness of the V-shaped corrugated core is 0.2-0.3mm, and the height is 0.4-0.6mm.

10. An application of the corrugated paperboard produced by the method for producing waterproof corrugated paperboard according to any one of claims 1 to 9 in corrugated paperboard boxes, characterized in that: After the corrugated paperboard is made into a corrugated paper box, the corrugated paper box is used to package food or pharmaceutical products to better ensure the hygiene and safety of food and pharmaceutical products.

Citation Information

Patent Citations

  • Wear resistant high-strength corrugated board and preparation method thereof

    CN110344279A

  • Composite corrugated paper and preparation method thereof

    CN113389092A